RETROSPECTIVES AND PERSPECTIVES OF TECHNICAL EDUCATION CONCEPTIONS - KOZUCHOVA, Maria (Trends in education, 2014)
The author of contribution based on the historical retrospectives of technical education concepts. Examines their focus and reasons, which has made the change in the curriculum. The greatest attention is given to research-tuned concept of technical education, which develops the six most important skills for scientific research. The last section is devoted to the forecasts of curriculum development in the future. The projections are based on assumptions of social development.
Keywords: technical education; curriculum; conception of education; perspective of education.